1.Преобразовать: 2. Упростить: sin2a cos2a sina cosa 4sin (4a-2 ctg(2a-31)-tg(2a+ X sinz sin-. cos a) 3.Докажите тождество 1-2sin²x 1+sin2x b) ЗД 2 (sina + cosa)2 - 1 ctga-sina.cosa 1-tgx 1+tgx 2tg²a X 3
Ответы
Ответ:
1. Преобразование:
sin(2a)cos(2a)sin(a)cos(a) + 4sin(4a - 2ctg(2a - 31) - tg(2a + X))sin(z)sin(-cos(a))
= 2sin(a)cos(a)sin(2a)cos(2a) + 4sin(4a - 2ctg(2a - 31) - tg(2a + X))sin(z)sin(a)cos(a) (переносим sin(a)cos(a) в начало первого слагаемого)
= sin(2a)sin(2a) + 2sin(4a - 2ctg(2a - 31) - tg(2a + X))sin(z)sin(2a) (упрощение)
= sin(2a)[sin(2a) + 2sin(4a - 2ctg(2a - 31) - tg(2a + X))sin(z)]
2. Упрощение:
sin²x - sin²x cos²x + sin²x cos²x - cos²x = sin²x (1 - cos²x) + cos²x (sin²x - 1)
= sin²x sin²x + cos²x(-sin²x) = sin⁴x - sin²x cos²x
3. Доказательство:
a) (sin(a) + cos(a))² - 1 = sin²(a) + cos²(a) + 2sin(a)cos(a) - 1
= 2sin(a)cos(a) = ctg(a)
b) (1 - tg(x))(1 + tg(x)) = 1 - tg²(x) = 1 - (sin(x)/cos(x))²
= (cos²(x) - sin²(x))/cos²(x) = cos(2x)/cos²(x)
(1 + sina + cosa)² - 1 = 1 + 2sin(a) + 2cos(a) + sin²(a) + 2sin(a)cos(a) + cos²(a) - 1
= 2sin(a) + 2cos(a) + 2sin(a)cos(a) = 2(sin(a) + cos(a))(1 + sin(a)cos(a))
= 2(ctg(a))(1 + tg(a))
(ctg(a) - sin(a)cos(a))/(1 - tg(x)) = cos²(a)/(sin(x) - cos(x))
= cos²(a)/(-sin(a)/cos(a)) = -cos³(a)/sin(a)
2tg²(a) - 3 = 2(sin²(a)/cos²(a)) - 3
= (2sin²(a) - 3cos²(a))/cos²(a) = -cos(2a)/cos²(a)